Orchestrating Digital Technology and Child-Centered Pedagogy: Management Strategies for Mindful, Meaningful, and Joyful Learning in Early Childhood Education - Asmila; Hadi Pajarianto; Harmita Sari (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to investigate management practices in early childhood education that promote attentive, meaningful, and joyful learning in the digital age. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews, participatory observation, and document analysis. The participants were the principal and teachers of a kindergarten in Palopo City, Indonesia, selected through purposive sampling due to their direct involvement in planning, managing, and implementing learning processes. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which involves data condensation, data display, and conclusion drawing/verification. The findings reveal that digital technology is used selectively as a pedagogical supplement rather than as the primary mode of instruction. Mindful learning is reflected in teachers’ preparedness, attentiveness, and responsiveness to classroom conditions. Meaningful learning is fostered through contextual and experience-based activities that connect learning content with children’s daily lives. Joyful learning is supported through play-based, multimodal, and emotionally supportive classroom practices. In addition, school management plays a strategic role through instructional planning, provision of digital facilities, teacher scheduling, professional development, and ongoing supervision. This study argues that effective early childhood education management in the digital era depends not on the intensity of technology use, but on the institution’s ability to integrate technology, pedagogy, and child-centered interaction in a coherent and developmentally appropriate manner.